2019
DOI: 10.1002/adfm.201904101
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Efficiency Roll‐Off and Improved Stability of Mixed 2D/3D Perovskite Light Emitting Diodes by Balancing Charge Injection

Abstract: Perovskite light emitting diodes (PeLEDs) have reached external quantum efficiencies (EQEs) over 21%. Their EQE, however, drops at increasing current densities (J) and their lifetime is still limited to just a few hours. The mechanisms leading to EQE roll‐off and device instability require thorough investigation. Here, improvement in EQE, EQE roll‐off, and lifetime of PeLEDs is demonstrated by tuning the balance of electron/hole transport into a mixed 2D/3D perovskite emissive layer. The mixed 2D/3D perovskite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 50 publications
2
124
1
Order By: Relevance
“…In addition, the co‐HTLs‐structure‐based device shows acceptable spectral stability when the applied voltage increases from 3.2 to 6.2 V (Figure f). Notably, our device exhibits low efficiency roll‐off, indicating a balanced charge injection and recombination . It is worth emphasizing that the stability of the EL spectra is mainly attributed to the balanced charge injection resulting from the co‐HTLs structure, as K + ‐based single HTL device undergoes phase segregation under constant voltage (Figure S13, Supporting Information).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, the co‐HTLs‐structure‐based device shows acceptable spectral stability when the applied voltage increases from 3.2 to 6.2 V (Figure f). Notably, our device exhibits low efficiency roll‐off, indicating a balanced charge injection and recombination . It is worth emphasizing that the stability of the EL spectra is mainly attributed to the balanced charge injection resulting from the co‐HTLs structure, as K + ‐based single HTL device undergoes phase segregation under constant voltage (Figure S13, Supporting Information).…”
Section: Resultsmentioning
confidence: 85%
“…Notably, our device exhibits low efficiency roll-off, indicating a balanced charge injection and recombination. [47] It is worth emphasizing that the stability of the EL spectra is mainly attributed to the balanced charge injection resulting from the co-HTLs structure, [17,48] as K + -based single HTL device undergoes phase segregation under constant voltage ( Figure S13, Supporting Information). Furthermore, through optimizing the device structure, the optimized blue perovskite NC-LED achieves a state-of-the-art EQE among the blue PeLEDs based on NCs.…”
Section: Device Performancementioning
confidence: 99%
“…To understand the role of Auger recombination and spatial carrier distribution qualitatively, recombination rate R ( n ) can be divided into three components: trap‐assisted non‐radiative recombination ( An ), radiative recombination ( Bn 2 ), and Auger recombination ( Cn 3 ) (Equation (2), where A , B , and C are coefficients): [ 25,28,40,41 ] R n= An+Bn2+Cn3…”
Section: Resultsmentioning
confidence: 99%
“…[ 23,24 ] To reduce carrier density in quantum wells (QWs), increased QW width was acquired via different methods like adjusting precursor ratios or partial cation exchange. Fakharuddin et al found 2D/3D mixed perovskite structure improved the carrier spatial distribution in the perovskite layer with the support of electroluminescent (EL) transients, [ 25 ] and stable EQE was achieved with the current density from 0.1 to 200 mA cm −2 . These studies point out that in perovskite LEDs, carrier density and carrier spatial distribution in emissive layer have great influences on the roll‐off behaviors of the devices.…”
Section: Introductionmentioning
confidence: 99%
“…92 Heremans, Gulbinas, Fakharuddin, and coworkers showed that balanced electron and hole injection reduced the roll-off issue. 93 The exact mechanism responsible for the EQE roll-off is still under debate and needs more research works.…”
Section: Working Stabilitymentioning
confidence: 99%